Femtosecond laser–assisted cataract surgeries reported to the European Registry of Quality Outcomes for Cataract and Refractive Surgery: Baseline characteristics, surgical procedure, and outcomes. Issue 12 (December 2017) - Lundström, Mats; Dickman, Mor; Henry, Ype; Manning, Sonia; Rosen, Paul; Tassignon, Marie‐José; Young, David; Stenevi, Ulf
Abstract : Purpose : To describe a large cohort of femtosecond laser–assisted cataract surgeries in terms of baseline characteristics and the related outcomes. Setting : Eighteen cataract surgery clinics in 9 European countries and Australia. Design : Prospective multicenter case series. Methods : Data on consecutive eyes having femtosecond laser–assisted cataract surgery in the participating clinics were entered in the European Registry of Quality Outcomes for Cataract and Refractive Surgery (EUREQUO). A trained registry manager in each clinic was responsible for valid reporting to the EUREQUO. Demographics, preoperative corrected distance visual acuity (CDVA), risk factors, type of surgery, type of intraocular lens, visual outcomes, refractive outcomes, and complications were reported. Results : Complete data were available for 3379 cases. The mean age was 64.4 years ± 10.9 (SD) and 57.8% (95% confidence interval [CI], 56.1‐59.5) of the patients were women. A surgical complication was reported in 2.9% of all cases (95% CI, 2.4‐3.5). The mean postoperative CDVA was 0.04 ± 0.15. logarithm of the minimum angle of resolution. A biometry prediction error (spherical equivalent) was within ±0.5 diopter in 71.8% (95% CI, 70.3‐73.3) of all surgeries. Postoperative complications were reported in 3.3% (95% CI, 2.7‐4.0). Patients with good preoperative CDVA had the best visual and refractive outcomes; patients with poor preoperative visual acuity had poorer outcomes. Conclusions : The visual and refractive outcomes of femtosecond laser–assisted cataract surgery were favorable compared with manual phacoemulsification. The outcomes were highly influenced by the preoperative visual acuity, but all preoperative CDVA groups had acceptable outcomes.